Efficacy and Safety of Sirolimus in Lymphangioleiomyomatosis - McCormack, Francis X; Inoue, Yoshikazu; Moss, Joel; Singer, Lianne G; Strange, Charlie; Nakata, Koh; Barker, Alan F; Chapman, Jeffrey T; Brantly, Mark L; Stocks, James M; Brown, Kevin K; Lynch, Joseph P; et al. (The New England journal of medicine, 2011)
This trial showed that in patients with lymphangioleiomyomatosis (LAM), a progressive, cystic lung disease in women, sirolimus therapy was associated with stabilization of lung function, reduction in symptoms, and improvement in qualityof-life measures. Lymphangioleiomyomatosis (LAM) is an uncommon systemic disease that is associated with cystic destruction of the lung, chylous pleural effusions, and abdominal tumors such as renal angiomyolipomas. 1 , 2 LAM affects women almost exclusively and occurs sporadically, developing in about 5 persons per 1 million; it also affects 30 to 40% of women with tuberous sclerosis complex (TSC). Lung function, measured as the forced expiratory volume in 1 second (FEV 1 ), declines at the rate of 75 to 118 ml per year 3 – 5 ; clinically important respiratory impairment, recurrent pneumothoraxes, and hypoxemia develop in most patients within a decade after the . . .